Selecting, Speaking and Saving: Applying Vocabulary Self-Collection Strategy in ESL Classroom at Intermediate Level at NUML - Sameen, Tahira; Ayaz, Amina (UMT Education Review, 2022)
This particular research was conducted under the light of Martha Rapp Haggard’s vocabulary approach known as Vocabulary Self-Collection Strategy (VSS). The aim of this particular research was to enhance the active usage of vocabulary in learners with the help of VSS. Moreover, the current study was based on the role of VSS in an English language learning classroom at intermediate level. A diagnostic pre-test was conducted on the ‘vocabulary self-collection group’ and the ‘controlled group’. The two groups were enrolled in two sections of the same reading and writing course of this diploma course. The learners who belonged to ‘vocabulary self-collection group’ were asked to self-collect words to improve their vocabulary, whereas the ‘controlled group’ was taught the vocabulary in usual manner. After two weeks of practice, the unseen post-test was administered from both the groups. The performance of both groups in the post-test was statistically analyzed and the results were quite optimistic, as vocabulary self-collection group outperformed the controlled group. The participants of this research were the researchers and the students of the intermediate level, from diploma classes at NUML. This particular research was based on qualitative and quantitative data. The quantitative data was gathered through the pre-test and the post-test and the qualitative data was attained by the observation of the researcher who analyzed the scores. The research tools were lesson plans, pre-test, and post-test. The current study material used in this course were five illustrated texts for intermediate level and vocabulary journals of the students. The sample size included 46 students of diploma level from National University of Modern Languages, Islamabad. The implementation of this particular strategy led to several improvements. Firstly, vocabulary of the learners improved and also it became a part of their active memory. Furthermore, it helped learners to define the words properly that were not known to them before, based on the context of the given text. Finally, group discussion activity improved ‘student-student interaction’ and ‘student-teacher interaction’ in the class. Keywords: active, vocabulary, vocabulary self-collection strategy, VSS